2016
DOI: 10.5152/tud.2016.98474
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of interstitial cells of Cajal in the bladders of fetal rats with retinoic acid induced myelomeningocele

Abstract: Objective: Myelomeningocele (MMC) is one of the most common reason of neurogenic bladder dysfunction in children. Although neurogenic bladder dysfunction occurrence is related with bladder innervation, also there are some changes seen in the smooth muscle and neural cells of the bladder. Interstitial cells of Cajal (ICC) are the pacemaker cells found in organs with peristaltic activity. Although it has been shown that ICC are diminished in the rat urinary bladder with traumatic spinal cord injury, there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Impairment of bladder wall muscular innervation can be seen as early as embryonic day 20 in fetal rats with MMC and persists at term [33]. Additionally, decreased concentrations of interstitial cells of Cajal, which mediate bladder contractility, have been noted in retinoic acid-induced MMC in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of bladder wall muscular innervation can be seen as early as embryonic day 20 in fetal rats with MMC and persists at term [33]. Additionally, decreased concentrations of interstitial cells of Cajal, which mediate bladder contractility, have been noted in retinoic acid-induced MMC in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the ICCs of the dome wall act as pacemaker cells leading to the detrusor instability. However, Tekin A, et al [ 46 ] found that the density of ICCs decreased in the neurogenic bladder of fetal rats with myelomeningocele. This phenomenon was explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased gap junction formation in the suburothelium was demonstrated, and it is hypothesized that this change could play a significant role in the sensory and motor pathway of the detrusor abnormality, as the mucosa may take over the neuronal role [ 46 ]. Fetal rats with induced MMC were found to have a significantly reduced number of ICCs, and it was hypothesized, that the observed bladder dysfunction may be related to the reduced density of ICCs in the developing bladder [ 47 ]. The only study performed on children with MMC and NLUTD could not confirm changes in ICC density compared to controls [ 48 ].…”
Section: Structural and Morphological Propertiesmentioning
confidence: 99%